2022
DOI: 10.1007/s10853-022-07439-7
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate-loaded gelatin microparticles as templating agents for macroporous magnesium phosphate-based bone cements

Abstract: Magnesium phosphate-based cements (MPCs) have recently attracted great attention as materials for bone repair. However, the lack of macroporosity, fundamental for cells permeation and bone ingrowth, is one of the main limitations hampering MPCs full exploitation. In this work gelatin microparticles are exploited as templating agents for the creation of macroporosities in MPCs. In addition, gelatin particles were loaded with a well-recognized drug for the treatment of osteoporosis, alendronate, to locally relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…These studies also proved that CAPP treatments increase the biological activity of MPC scaffolds in terms of the osteogenic stimulus. Overall, we demonstrated that MPCs, already proven as injectable and moldable materials, 15,40 preserve a good biocompatibility upon CAPP treatment despite modifying their phase composition. As a future perspective, the comparison of the effect of CAPP toward MPCs vs CPCs would also be of great interest to further demonstrate the potential of such materials and the use of CAPP treatments on them.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…These studies also proved that CAPP treatments increase the biological activity of MPC scaffolds in terms of the osteogenic stimulus. Overall, we demonstrated that MPCs, already proven as injectable and moldable materials, 15,40 preserve a good biocompatibility upon CAPP treatment despite modifying their phase composition. As a future perspective, the comparison of the effect of CAPP toward MPCs vs CPCs would also be of great interest to further demonstrate the potential of such materials and the use of CAPP treatments on them.…”
Section: Discussionmentioning
confidence: 63%
“…6 The interest in MPCs toward biomedical applications is rapidly growing, 12−18 and various strategies have been recently developed to further improve MPCs' features, such as the inclusion of polymeric additives to enhance the injectability and printability 19,20 or the addition of porogens and templating agents to the formulation to induce the presence of macroporosity in the cement matrix. 15,21,22 Along with the modifications of the bulk material, the cement surface is of great importance, as it represents the first region that cells encounter when they get in contact with the material, being crucial for their adhesion, spreading, and ultimately for the material biocompatibility. 23 Surface modifications aim at creating a specific chemical and physical environment that offers a favorable cellular response in tissues and include changes in topography and morphology, functionalization, and coatings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, the % of extruded paste with respect to the amount initially loaded in the syringe is calculated, and the injectability % is obtained. The injection can be performed manually [ 109 , 158 ] or in controlled conditions, using specific loads and testing machines [ 58 , 160 , 162 ]. Mestres et al compared Na-MPCs, NH 4 -MPCs, and a mixed system, observing that Na-based MPCs had a higher injectability % [ 58 ].…”
Section: Magnesium Phosphate Cements: Preparation and Propertiesmentioning
confidence: 99%